THE EFFECT OF SERVICE QUALITY AND PRICE ON CONSUMER SATISFACTION AT J&T CARGO BRANCH SUB B PETEMON SURABAYA - Zumrotul Khoiriyah; Is Fadhilah (Pedagogic Research-Applied Literacy Journal, 2025)
This study investigates "The Effect of Service Quality and Price on Consumer Satisfaction at J&T Cargo Branch Sub B Petemon Surabaya." Consumer satisfaction is crucial to the branch's success in providing shipping services. A decline in customers over the past three months has been linked to low levels of consumer satisfaction, influenced by service quality and pricing. Improved service quality and competitive pricing are expected to enhance consumer satisfaction, thereby fostering loyalty and encouraging repeat usage of services. Utilizing a quantitative approach, the study surveyed 120 active respondents through questionnaires. Data analysis was performed using multiple linear regression with SPSS Version 25. Findings indicate that both service quality and price significantly and positively affect consumer satisfaction.